Beyond clinical genomics: addressing critical gaps in One Health AMR surveillance - Vallejo-Espín, Diana; Galarza-Mayorga, Jael; Lalaleo, Liliana; Calero-Cáceres, William (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) poses an escalating global threat that demands comprehensive surveillance approaches beyond traditional clinical contexts. Although next-generation sequencing (NGS), particularly whole-genome sequencing (WGS), has revolutionized AMR surveillance, current implementation predominantly targets clinical isolates, largely neglecting critical environmental and animal reservoirs. Consequently, significant gaps persist in our understanding of AMR dynamics across diverse ecosystems. This Perspective emphasizes the urgent need to adopt an integrated genomic framework, combining isolate-based WGS with shotgun metagenomics within a cohesive One Health strategy. Such an integrated approach would significantly enhance the detection, tracking, and containment of resistance determinants, facilitating proactive rather than reactive AMR management. Achieving this vision requires global standardization of sequencing methods, harmonization of bioinformatics pipelines, and strengthened cross-sectoral collaboration to ensure timely interventions against AMR threats worldwide.